A review of graphene biopolymer composite in piezoelectric sensor applications - Muhammad Firdaus, Abdul Halim; Mohd Sapuan, Salit; Mohd Afdzaluddin, Atiqah; M. AL-Oqla, Faris (Walter de Gruyter, 2024)
The amazing electrical, optical, mechanical and thermal properties combined with high specific surface area of graphene making it as an appealing integrant for stimuli responsive high performance smart materials. Typical graphene-based smart materials encompass mechanically exfoliated perfect graphene, chemical vapor deposited first-class graphene, chemically moded graphene including graphene oxide and reduced graphene oxide and their macroscopic assemblies or composites. The ability of these graphene-based materials ending up interacting with biopolymers to come up with quite fascinating electrical, mechanical, optical, thermal and sensing characteristics has have attracted a considerable number of attentions. The biggest advantage of using biopolymer-based materials is non-corrosiveness, ease in coloration, good tensile strength, and biodegradability but are abided by drawback of the poor mechanical strength, lack of response, and unstable environmental stability. However, graphene incorporated biopolymers provided beneficent attributes for example ability to detect various forms of stimuli such as gaseous molecules include biomolecules, pH value, mechanical flexibility, electrical and thermal conductivity to enable ongoing promising advancement of the piezoelectric sensor applications. This review explores the piezoelectric development based on several graphene fabricated biopolymer composite and it is use in healthcare monitoring, structural health monitoring, industrial process monitoring, consumer electronics applications. Furthermore, we enlighten the challenges and future perspectives of graphene biopolymer piezoelectric sensors.